Auditory sensory gating in Huffaz using an auditory brainstem response with a psychological task: a preliminary investigation - Dzulkarnain, Ahmad Aidil Arafat; kamal Azizi, Amirah; Sulaiman, Nur Hafizah (2021)
Background: Auditory brainstem response (ABR) can be influenced by cognitive task due to the sensory inhibition process known as auditory sensory gating. Investigation of ABR with cognitive tasks among individual with strong memory abilities such as Huffaz (someone who memorized the whole chapters of Islamic scripture of Holy Al-Quran) is lacking in the literature. Therefore, the aim of this study is to investigate sensory gating abilities using ABR with a psychological task in Huffaz and Non-Hufaz population. Methods: A total of 11 Huffaz and 12 Non-Huffaz with normal earing and normal ear function participated in this study. The ABR was acquired from the participants using a tone burst stimulus (2-1-2 cycles) at 3000 Hz with a stimulus repetition rate of 39.9 Hz. The ABR was conducted under two recording conditions of (i) without cognitive interference and (ii) with cognitive interference. The cognitive interference was elicited using a Stroop task procedure. The ABR wave V amplitudes and latencies were compared between test conditions and groups at 95% of confidence intervals. Results: The findings showed no changes in the ABR wave V amplitudes and latencies between the test conditions in both groups with a lack of statistical differences. Conclusion: There was no difference in the auditory sensory gating abilities between Huffaz and Non-Huffaz as shown by the ABR sensory gating outcomes. The absence of statistical differences between both groups in sensory gating abilities could be because Quranic memorization is only affecting the long-term memory compared to the short-term working memory abilities.